Integrating Artificial Intelligence in Education: Understanding Students' Perceptions - Sain, Zohaib Hassan; Vasudevan, Asokan; Serban, Razvan; Thelma, Chanda Chansa (Journal of Education and Islamic Studies (JEIS), 2024)
ABSTRACT The advent of cutting-edge technologies has prompted the transformation of current educational systems by integrating these advancements into contemporary teaching and learning methodologies. Given the substantial potential of Artificial Intelligence (AI) to revolutionize these practices, the consideration of its incorporation into the educational domain is inevitable. This research delves into the latest developments in AI within education, examining how secondary school students involved in this research utilize AI and for what specific purposes. Additionally, this study seeks to understand whether these students employ Artificial Intelligence for educational and learning purposes and their opinions on its inclusion in educational frameworks. The collected data provide valuable insights into students' comprehension of AI's role and objectives in education and their perspectives on its application across various scenarios. Furthermore, the study underscores the significance and challenges of integrating Artificial Intelligence into curricula, highlighting the opportunities it presents for crafting educational practices that enhance students' academic knowledge and digital proficiency while emphasizing the ethical and responsible use of such technologies. ABSTRAK Munculnya teknologi mutakhir telah mendorong transformasi sistem pendidikan saat ini dengan mengintegrasikan kemajuan ini ke dalam metodologi pengajaran dan pembelajaran kontemporer. Mengingat potensi besar Kecerdasan Buatan (AI) untuk merevolusi praktik-praktik ini, pertimbangan untuk memasukkannya ke dalam bidang pendidikan tidak dapat dihindari. Penelitian ini menggali perkembangan terkini AI dalam dunia pendidikan, mengkaji bagaimana siswa sekolah menengah yang terlibat dalam studi kasus ini memanfaatkan AI dan untuk tujuan spesifik apa. Selain itu, penelitian ini berupaya memahami apakah para siswa ini menggunakan Kecerdasan Buatan untuk tujuan pendidikan dan pembelajaran serta pendapat mereka tentang penyertaannya dalam kerangka pendidikan. Data yang dikumpulkan memberikan wawasan berharga mengenai pemahaman siswa tentang peran dan tujuan AI dalam pendidikan serta perspektif mereka terhadap penerapannya dalam berbagai skenario. Lebih jauh lagi, penelitian ini menggarisbawahi pentingnya dan tantangan dalam mengintegrasikan Kecerdasan Buatan ke dalam kurikulum, menyoroti peluang yang ada untuk menciptakan praktik pendidikan yang meningkatkan pengetahuan akademis dan kemahiran digital siswa sambil menekankan penggunaan teknologi tersebut secara etis dan bertanggung jawab.